EVALUASI DAN PEMETAAN POTENSI DESA MITRA DPPM UII - Yulianto Purwono Prihatmaji; Akhmad Fauzy; Feris Firdaus; M. Bambang Subekti (UII, 2015)
Desa Mitra (Partners Village) DPPM UII is the embodiment of catur dharma UII, which is a program of community development and rural area development based on thematic local potential and sustainable. DesaMitra program has been done a long time, but intensively measured and planned starting in 2006. Collaborative research with the community, the diffusion of science and technology, community service is a program developed in the DesaMitra program supported from internal funds UII, external funds DIKTI and / or CSR from various companies. To measure the achievement of the objectives and benefits of the DesaMitra program is needed evaluation and mapping studies. Evaluation includes the fruit-fullness of the program, the community understanding and their awareness for self-sustained. Evaluation by purposive random sampling of the dozens DesaMitra acquired 7 villages, namely: Sendangagung, Sendangsari, Wukirsari, Sindumartani, Cokrodiningratan, which is located in the district of Sleman and Yogyakarta municipality. The results obtained 5 villages to be developed in near future considered their potential has not been developed, high motivation from community and supportsother related program. The 2 villages postponed to be developed assessed effectiveness of development assistance program and the level of self-developed of its people. Keywords: evaluation, mapping, desamitra, mentoring, self-reliance